SISTEM INFORMASI ABSENSI PEGAWAI DESA CILEMPUYANG BERBASIS WEB - Riswanto, Beny (Jurnal Teknologi dan Bisnis, 2019)
The cilempuyang Village Office is one of the offices located in cimanggu District, Cilacap Regency, Central Java Province, in managing and storing media information related to data, profiles, attendance and employee activities are still done manually. Manual attendance is considered ineffective and takes time, when checking and searching for employee data, the employee is still manual using books and stationery. The purpose of this attendance system is to make it easier for the admin in charge of checking village employees. This research was conducted at the Sadahayu Village Office, the system is designed based on a website as a medium for attendance of village officials, the programming language used is PHPMySQL as a database, it is hoped that it will make it easier for admins to manage attendance and employee data efficiently. This system is good enough and can simplify the attendance process